2017
DOI: 10.1002/jmri.25611
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐brain vessel wall MRI: A parameter tune‐up solution to improve the scan efficiency of three‐dimensional variable flip‐angle turbo spin‐echo

Abstract: Purpose To propose and evaluate a parameter tune-up solution to expedite a three-dimensional (3D) variable-flip-angle turbo spin-echo (TSE) sequence for whole-brain intracranial vessel wall (IVW) imaging. Materials and Methods Elliptical k-space sampling and prolonged echo train length (ETL), were used to expedite a 3D variable-flip-angle TSE-based sequence. To compensate for the potential loss in vessel wall signal, optimal combination of prescribed T2 and ETL was experimentally investigated on 22 healthy v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…The technique, based on sampling perfection with application‐optimized contrast using different flip angle evolutions, coupled with nonselective excitation and a trailing magnetization flip‐down module, has demonstrated improved spatial coverage, T1 contrast weighting, and signal suppression of cerebrospinal fluid. In principle, these all favor the delineation of the aforementioned plaque features 20, 21. The atherosclerotic lesions in all large intracranial arteries involved in bilateral anterior circulation were investigated to reveal the plaque features that are highly associated with symptomatic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The technique, based on sampling perfection with application‐optimized contrast using different flip angle evolutions, coupled with nonselective excitation and a trailing magnetization flip‐down module, has demonstrated improved spatial coverage, T1 contrast weighting, and signal suppression of cerebrospinal fluid. In principle, these all favor the delineation of the aforementioned plaque features 20, 21. The atherosclerotic lesions in all large intracranial arteries involved in bilateral anterior circulation were investigated to reveal the plaque features that are highly associated with symptomatic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that flow-sensitive black blood magnetic resonance angiography (FSBB-MRA) based on 3D gradient-echo sequence can be specifically used to visualize LSAs [ 14 16 ]. Our recent studies have demonstrated the feasibility of whole-brain high-resolution magnetic resonance imaging (WB-HRCMR),which enables combined evaluation of plaque and LSAs in one image setting [ 17 , 18 ]. Thus, in this study, we aimed to use WB-HRCMR to quantitatively investigate different features of plaque and LSAs in symptomatic versus asymptomatic ICAS groups.…”
Section: Introductionmentioning
confidence: 99%
“…The morphologic measurements, including the lumen diameter of the CCA and segments C1-C7, and the stenosis diameter, stenosis degree, reference diameter, and lesion length, as measured by 3D CMR VWI, displayed excellent accordance with those measured by DSA (ICC > 0.84). One possible reason for the excellent performance of the 3D CMR VWI technique is that a non-selective excitation radio-frequency pulse has been used to shorten the echo time, which helps improve the SNR of images [23,24,27]. Additionally, 3D CMR VWI provided a high isotropic resolution of 0.63 × 0.63 × 0.63 mm 3 , and achieves good flexibility with regard to image visualization, which thereby enables the visualization of plaques located in the tortuous and deep-seated intracranial carotid.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a three-dimensional (3D) CMR vessel wall imaging (VWI) technique based on 3D T1 weighted (T1w) Sampling Perfection with Application-optimized Contrast using different flip-angle Evolutions (SPACE) has become technically feasible and gained increasing attention for the diagnosis of atherosclerosis [22][23][24][25][26]. This technique is advantageous over conventional two-dimensional techniques, as it has sufficient BB effects, large spatial coverage, high isotropic resolution and signal-to-noise ratio (SNR), excellent scan efficiency, and remarkable cerebrospinal fluid (CSF) signal attenuation [23,24,27]. It therefore shows a unique capability for evaluating both lumen and wall features.…”
Section: Introductionmentioning
confidence: 99%